The M2 Model for Dose Simulation in Radiation Therapy. Issue 3 (15th April 2016) - Pichard, T.; Alldredge, G. W.; Brull, S.; Dubroca, B.; Frank, M.
ABSTRACT: The transport of photons and electrons is studied in the field of radiotherapy to compute the dose, that is, the quantity of energy transferred to the medium by a beam of particles at each position. A kinetic model is proposed, and to decrease the computation times, it is reduced through a moment extraction. Entropy-based angular moment models of order up to two ( M 1 and M 2 models) are shown to provide accurate results compared to a reference code with much lower computational costs.